Because Claudette - Baptiste, Tracey; Engel, Tonya (New York : Dial Books for Young Readers, 2022)
"A picture book biography about Claudette Colvin, the teen whose activism launched the Montgomery bus boycott, and a celebration of collective action"--
Keywords: Colvin, Claudette, -- 1939- -- Juvenile literature; Colvin, Claudette, -- 1939-.; African American teenage girls -- Biography -- Alabama; African Americans -- Biography -- Alabama; Montgomery Bus Boycott, Montgomery, Ala., 1955-1956 -- Juvenile literature; Segregation in transportation -- Juvenile literature. -- History -- Alabama; African American teenage girls -- Biography. -- Alabama; African Americans -- Biography. -- Alabama; Montgomery Bus Boycott, Montgomery, Ala, 1955-1956.; Segregation in transportation -- History. -- Alabama; Montgomery (Ala.) -- Race relations -- 20th century; Montgomery (Ala.) -- Biography; Montgomery (Ala.) -- Juvenile literature. -- Race relations -- 20th century; Montgomery (Ala.) -- Biography; Biographies